Analysis of the design and engineering-process towards a first prototype in the field of sports and vitality - Janssen, M.; van den Heuvel, R.; Megens, C.; Levy, P.; Vos, S. (Proceedings, 2018)
The scope of technology has expanded towards areas such as sports and vitality, offering significant challenges for engineering designers. However, only little is known about the underlying design and engineering processes used within these fields. Therefore, this paper aims to get an in-depth understanding of these type of processes. During a three-day design competition (Hackathon), three groups of engineers were challenged to develop experience-able prototypes in the field of sports and vitality. Their process was monitored based on the Reflective Transformative Design process (RTD-process) framework, describing the various activities part of the design process. Groups had to keep track of their activities, and six group reflection-sessions were held. Results show that all groups used an open and explorative approach, they frequently swapped between activities, making them able to reflect on their actions. While spending more time on envisioning and creating a clear vision seem to relate to the quality of the design concept.